Fuzzy Available-to-Promise System Modelling Under Supplier Uncertainty - Halim , Tony; Kanesan , Muthusamy (Trans Tech, 2012)
Available-To-Promise (ATP) function is an important tool in supply chain management to enhance the responsiveness of order promising and the reliability of order fulfillment. ATP models provide responses to customer order enquiries, based on resource availability, allowing the user to determine whether they should accept the order. Currently, many of the ATP models available adopt a deterministic approach and do not address uncertainties in the manufacturing environment. In this paper, a fuzzy mathematical programming model is proposed to address the problem of order-promising under an environment of supply uncertainty. The model aims to minimize the cost of rejecting orders, failing to meet promised orders and inventory holding cost of the finished products and supply materials. In addition to order promising, the model also performs order-fulfillment and provides a master production schedule of each product and material requirement planning of each supply material over the given planning horizon. To solve the fuzzy mathematical model, an approach based on possibility and necessity theory is applied.